Empowering Women through Islamic Education: Building Equality and Sustainable Achievement - Al Jumhuri, Muhammad Asroruddin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Empowering women through Islamic education is pivotal for fostering equality and sustainable achievement. This study explores the transformative role of Islamic education in advancing women's empowerment within Muslim communities, focusing on building equality and fostering sustainable development. Utilizing a comprehensive literature review and qualitative research methods, the study investigates how Islamic education empowers women by challenging traditional gender norms and promoting gender equality through ethical teachings. Additionally, it examines pedagogical approaches within Islamic educational institutions that foster women's leadership, critical thinking, and agency. Moreover, the research delves into the societal impact of empowered women, highlighting their contributions to social cohesion, economic development, and community well-being. Through qualitative interviews and case studies, the study showcases success stories of women benefiting from Islamic education and becoming agents of positive change. The findings have significant implications for policymakers, educators, and community leaders, suggesting the need for inclusive educational policies and support systems that promote gender equality and sustainable development through Islamic education. In conclusion, empowering women through Islamic education is essential for building equitable and resilient societies, reflecting the transformative potential of Islam in advancing equality and sustainable achievement within and beyond Muslim communities.